Características produtivas e parâmetros bromatológicos de pastagens de Tifton 85 (Cynodon spp) e Coastcross (Cynodon dactylon) e desempenho de bovinos da raça Purunã - Teixeira, Marcos Antonio (2014)
The objective of this paper was to evaluate the animal performance of Purunã race as well as pastures of Tifton 85 (Cynodon spp) and Coastcross (Cynodon dactylon) with and without irrigation, being the experiment conducted in the city of Santa Tereza do Oeste/PR. Initially, it was evaluated the production of dry material (MS) and the bromatological composition of the pastures of Tifton 85 grass and coastcross with and without irrigation. The experimental delimitation was made in randomized blocks, with two forage species (Tifton 85 grass and the coastcross) and two systems of pasture (with and without irrigation) allocated in subplots into four evaluation periods (December 2012, January, February and March 2013), with three repetitions. The pasture management was done under continuous capacity and variable animal charge in 15 pickets, totaling 9,75 hectares, with three animals of Purunã race tested by treatment, in a total of 45 animals, plus the regulators animals. It s worth to notice that during the period that the experiment was developed, there was a monthly average of 233 mm of rainfall. The pasture implementation in the experimental area occurred in January and February 2012, and it was used liming and fertilization according to the soil analysis. The irrigation was realized by sprinkling with mesh system distribution. For the pasture management, it was utilized the continuous capacity method, with an offer of 6% (6 kg MS/100 kg/pc). It were used Purunã heifers with initial corporal weight of about 200 kg. The animal performance evaluation was realized through weight control, so the input and output weighing of test and regulator animals was done only at the beginning and at the end of the experiment, both preceded of 12 fasting hours. The animal average daily gain (GMDA) was gotten by averaging the difference between the input and output of test animals and by the number of days they remained in the pickets. There was a higher accumulation of MS for the period 2 (P2) over other periods, except on the treatment of coastcross with irrigation (TCI) on period 3 (P3). It was also observed, on treatments and periods, a variation in the protein levels from 15,2 to 20,2% on the leaf and from 9,2 to 11,9% on the stem. In relation to the weight gain, there was no significant difference between treatments and periods, but it was observed a difference of 15% on the weight gain for irrigated pastures in relation to nonirrigated. The individual weight gain, done of pasture and without supplementation, presented by Purunã heifers, was up to 0,833kg/day-1